Internal Magnetic Lengthening and Reconstruction with Free TRAM Flap After Traumatic Transfemoral Amputation: A Case Report. Issue 2 (April 2021) - Kuruoglu, Doga; Sems, Stephen A.; Sampson, Brandon P.; Carlsen, Brian T.
Abstract : Case: This is a case of a 41-year-old man who sustained a traumatic proximal transfemoral amputation with loss of adductor function and inadequate soft tissue. Wound closure was achieved with split-thickness skin grafting. Subsequently, femoral lengthening was achieved with an internal magnetic lengthening nail. He underwent a free transverse rectus abdominis myocutaneous (TRAM) flap to resurface the limb and provide more stable soft tissue, adductor repair, and further lengthening because of his prominent abduction contracture and inadequate soft tissue. This allowed independent ambulation with a prosthetic. Conclusion: Femoral lengthening with soft-tissue reconstruction improved prosthetic function and ambulation in a patient with a short transfemoral amputation.